2018
DOI: 10.1016/j.jare.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid in health and disease with focus on hypertension and diabetes mellitus: A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 193 publications
(257 reference statements)
7
69
0
1
Order By: Relevance
“…LA is converted to DGLA (C20:3n6) and AA (C20:4n6), while ALA is converted to form EPA (C20:5n3) and DHA (C22:6n3). Excessive intake of HFD reduces the levels of AA, EPA and DHA(42), enhances the production of pro-inflammatory arachidic acids and ROS, leading to proinflammatory status (42,43). Our results also confirmed that HFD impaired the desaturated metabolic pathway of EFAs: the ratio of AA/LA and DHA/ALA in HFD hamsters was down-regulated, and the expressions of FADS1 and FADS2 were significantly decreased.…”
Section: Discussionsupporting
confidence: 77%
“…LA is converted to DGLA (C20:3n6) and AA (C20:4n6), while ALA is converted to form EPA (C20:5n3) and DHA (C22:6n3). Excessive intake of HFD reduces the levels of AA, EPA and DHA(42), enhances the production of pro-inflammatory arachidic acids and ROS, leading to proinflammatory status (42,43). Our results also confirmed that HFD impaired the desaturated metabolic pathway of EFAs: the ratio of AA/LA and DHA/ALA in HFD hamsters was down-regulated, and the expressions of FADS1 and FADS2 were significantly decreased.…”
Section: Discussionsupporting
confidence: 77%
“…In general, prostaglandins and leukotrienes synthesized from AA exert proinflammatory actions and play a significant role in atherosclerosis, asthma, inflammatory bowel disease and hypertension. Another polyunsaturated fatty acid, docosahexaenoic acid, is a precursor of anti‐inflammatory compounds and is generated from its precursor, α ‐linolenic acid (Das, ; Nyamundanda, Brennan, & Gormley, ). It is likely that there exists a balance between proinflammatory and anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the Western diet is relatively poor in n-3 PUFAs and rich in n-6 PUFAs [12]. Because arachidonic acid (ARA, C20:4n-6) is a precursor to proinflammatory mediators, the role of an increased dietary intake of ARA, or of its metabolic precursor (linoleic acid (LA), C18:2n-6), in elevating the inflammatory process is debated [1,13].…”
Section: Introductionmentioning
confidence: 99%